Application of Taguchi Technique to Investigate the Effect of Process Parameters on Product Yield and Carbon Content in Empty Palm Oil Fruit Bunch Carbonization - Alfaresi, M; Yusup, Suzana (Asian Network for Scientific Information, 2010)
Carbonization is an important process which is used in a number of industries where, raw material from coal or agricultural origin are treated to remove moisture, volatile matter or undesirable material to yield a charcoal like product which may be further processed to produce valuable products such as activated carbon. In the current study, selected carbonization parameters are studied to investigate their effect on product yield and carbon content. Empty Palm Fruit Bunch (EPFB) was selected as the process feedstock for its wide availability; being a byproduct from palm oil industry. The studied parameters are carbonization temperature, nitrogen flow rate and soaking time. Taguchi technique for design of experiments and offline process analysis/optimization was used to build the approach of experiments by utilizing a modified L9 orthogonal array. The significance of each parameter was calculated by analyzing the results statistically to obtain the signal to noise ratio for each run as well as each level of parameter. The results showed that temperature had the most significant effect over product yield followed by nitrogen flow rate. The soaking time effect was statistically lower than that of gas flow rate but quantitatively close in value. For the carbon content of the product, soaking time showed to have the most significant effect. Temperature effect was second while gas flow rate seems to have the least effect statistically and quantitatively. Proposed carbonization conditions based on the results obtained in the current study are temperature of 650°C, nitrogen flow rate of 0.6 L min-1 and 30 min soaking time which gave 60.4% carbon content and 26.7% product yield.